Tinjauan Kriminologi Perkara Tindak Pidana Penyebaran Video Porno Melalui Media Sosial - Hana Regina Jawza; Setiawan, Dian Alan (UNISBA Press, 2024)
ABSTRACT. The Criminological Review of the Crime of Pornography Through Social Media Applications is based on the large amount of pornographic content that is widely spread on social media applications and the public's lack of understanding about the criminal act of pornography itself. The crime of pornography is regulated in Law No. 44 of 2008 concerning pornography, generally stated in article 4 paragraphs (1) and (2). Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. The problem formulation of this research is what are the factors that cause perpetrators to commit the criminal act of distributing pornographic videos via social media and what are the crime prevention efforts against the criminal act of distributing pornographic videos via social media. Using criminal law policy theory and the theory of the causes of crime (criminology). The research method used in this research is the juridical-normative method, namely by examining statutory regulations, legal theories, legal principles, and relevant legal doctrines to answer the legal problems being researched. The results of this research conclude that the factors causing the perpetrators to commit the criminal act of distributing pornographic videos via social media, namely the main motive of the perpetrators, the lack of legal awareness of the perpetrators, and the ease of use of social media. Responding to the existing phenomenon requires legal firmness, especially from officials who act in law enforcement as well as the important role of all levels of society to be aware of the dangers of pornographic content and to be more concerned about the surrounding environment. In tackling the criminal act of distributing pornographic videos via social media, this can be done by protecting victims, monitoring content on social media, counseling and education, as well as strict law enforcement.